ETIKA KONSUMSI (ISTIHLAK) PERSPEKTIF FILSAFAT EKONOMI ISLAM - Ainun Barakah; Pipin Suitra; Ulfatun Najiha (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2020)
Islam is a religion that teaches about balance, when he sets the rules or rules for the producers or owners of goods in terms of production, sales, distribution of a commodity, then on the other hand Islam is very concerned about ethics for consumers in buying food or product to be consumed. This paper discusses several ethics in consuming, both in terms of consumers and something consumed, whether it is in the halal and thoyyib criteria, and is in accordance with Islamic ethics. The method used is descriptive qualitative, with data sources (library research), namely the study of literature sourced from several related literature, both from articles or classic books (turats).